ANTIMICROBIAL ACTIVITY OF CINNAMALDEHYDE, VANILLIN AND KIGELIA AFRICANA FRUIT EXTRACTS AGAINST FISH-ASSOCIATED CHRYSEOBACTERIUM AND MYROIDES SPP. ISOLATES - Chenia, Hafizah Yousuf (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Members of the family Flavobacteriaceae exhibit intrinsic multi-drug resistance, which hampers their effective eradication. Phytochemicals are being explored as alternatives to the use of antimicrobial agents in aquaculture since they have growth-promoting, immune-stimulating, and antimicrobial properties. Materials and Methods: The susceptibility of 36 Chryseobacterium and seven Myroides spp. isolates from salmon, tilapia and trout as well as 19 selected Flavobacteriaceae type strains to cinnamaldehyde, vanillin and four crude Kigelia africana extracts (ethyl acetate, dichloromethane, methanol and hexane), was assessed using disc diffusion assays and compared to standard antimicrobial agents, ampicillin and tetracycline using activity indices. Results: Cinnamaldehyde (≥250 µg/ml) was the most effective (77. 8 – 100% susceptibility) while vanillin was the least effective with inhibitory activity only at 1000 µg/ml. The K. africana hexane extract (4 mg/ml) was the most effective, with only 11.3% of isolates displaying resistance, while 94.4% of isolates demonstrated resistance to ampicillin and 38.9% susceptibility to tetracycline. K. africana extract inhibitory efficacy decreased in the following order: hexane > ethyl acetate > dichloromethane > methanol. Cinnamaldehyde and K. africana EX 4 activity indices ≥ 1 were obtained for 83.3 - 97.2% and 25% of Chryseobacterium spp. isolates, respectively, relative to tetracycline. Conclusions: Cinnamaldehyde and K. africana fruit hexane extracts are promising candidates to be tested for their efficacy in the treatment of Chryseobacterium/Myroides-associated fish infections. These phytochemicals might serve as environmentally-friendly, cost-effective alternatives to the use of antimicrobial agents in aquaculture farms, with a lesser chance of resistance development.